Exposure Due to Indoor Radon in Bulgarian Schools - Kremena Ivanova; Nina Chobanova; Bistra Kunovska; Jana Djounova; Zdenka Stojanovska (Aerosol and Air Quality Research)
Abstract Indoor radon exposure is the largest contributor to population dose from natural sources. Radon as a natural radioactive gas could accumulate to harmful levels in buildings, such as homes and buildings with public access. In order to assess the exposure due to radon in school the results of indoor radon measurements in 55 state school buildings in 7 municipalities located in one district in southern Bulgaria are considered in this paper. The survey was carried out with passive CR-39 etched track detectors. Radon concentrations ranged from 17 to 868 Bq m−3, with a geometric mean of 117 Bq m−3 and a geometric standard deviation of 1.78. The findings revealed that in 30% of the measured buildings the radon concentration was higher than the national reference level of 300 Bq m−3. The statistically significant difference in indoor radon concentrations between municipalities (KW, p < 0.001) was obtained. The research was also focused on parameters affecting radon concentration levels such as type of room and floor location. The estimated annual effective dose of 0.39 to 1.07 mSv y−1, applying the ICRP and UNSCEAR methodology, was calculated for students. The results of the measurements were provided to the administrative authorities and measures were proposed to improve the air in school buildings with high radon levels.